Statement of the value of strategic openness in strengthening core capabilities - An analytical study of the opinions of a sample of educational institutions in Iraq - Hamid, Khaldoun Hussein; sultan, Reem yousif (The journal of contemporary issues in business and government, 2021)
This research focused on explaining the role of the value of strategic openness in enhancing the core capabilities, and the aim of answering it was to elucidate the theoretical and philosophical implications of these variables, and this research falls into two main parts: the first part included the research methodology, and theoretical approaches to the research variables and their exclusion, while the second part presented Analytical framework for research hypotheses, conclusions and recommendations. The study sample represented a group of workers in educational institutions in Iraq (University of Baghdad, University of Tikrit, University of Mosul), by examining the influence and correlation relationships between research variables, and the descriptive analytical approach was adopted, as well as selecting a sample of (216) workers. By adopting the questionnaire as a measurement tool, and the data were processed through the statistical program (SPSS) to prove the validity of the research hypotheses related to the influence and correlation between the two research variables, and the use of multiple regression coefficient and correlation coefficient as statistical methods. The most important conclusions reached by the research in the theoretical and field framework, the most important of which is the achievement of a positive moral correlation between the combined strategic openness and the combined core capabilities of the educational institutions under discussion in terms of their variables according to the value of the correlation coefficient at the macro level. Based on the findings of the research, the research presented some recommendations, the most important of which is the need for officials in educational institutions to focus on paying attention to the concept and value of strategic openness.